The assessment of fetal brain growth in diabetic pregnancy using in utero magnetic resonance imaging. Issue 5 (May 2017) - Paddock, M.; Akram, R.; Jarvis, D.A.; Armitage, P.; Song, S.; Madhuvrata, P.; Griffiths, P.D.
Abstract : Aim: To assess fetal brain growth over the third trimester in pregnant women with diabetes using in utero magnetic resonance imaging ( iu MRI) to determine if greater brain growth occurs in type 1 (T1DM) when compared to gestational (GDM) diabetes mellitus. Materials and methods: Each consented participant was scanned at three fixed times during the third trimester using iu MRI. One hundred and fifty-seven patients were approached, 48 participants were recruited, and 36 complete data sets were analysed. Three-dimensional (3D) iu MRI volume data sets were manually segmented using software to construct models of the fetal brain from which brain volumes could be calculated. Inter-rater analysis was performed, and volume differences and growth rates were compared between T1DM and GDM. Results: Recruitment proved difficult with low uptake and high attrition rates (77.1%). Inter-rater analysis revealed excellent correlation (intraclass correlation coefficient=0.93, p <0.001) and agreement with no significant difference between operators ( p =0.194). There was no evidence of increased brain volume in the T1DM group. Growth rates between visit 1 and 3 for T1DM and GDM were not significantly different ( p =0.095). Conclusion: T1DM brain volumes were not significantly larger than GDM volumes and there was no significant divergence of brain growth over the third trimester. Constructing volume models from 3D iu MRI acquisitions is a novel technique that can be used to assess fetal brain growth. No specialist software or knowledge is required. Larger studies attempting to recruit pregnant women in the later stages of pregnancy should employ multicentre recruitment to overcome recruitment difficulties and high attrition rates. Highlights: No differential fetal brain growth occurs over the third trimester of diabetic pregnancy. Manual segmentation of 3D iu MR acquisitions requires no specialist knowledge. 3D volume modelling of the fetal brain is a reliable and reproducible technique.